Trust-inducing interface on halal portal from user's perspective / Syahida Sulaiman - Sulaiman, Syahida (2008)
The rapid growth of Internet and the increment of its importance as time pass by are undeniable nowadays. The role that Internet plays as a getaway for people to get information is making it more vital day by day. The creation of the concept of portal soon became popular, as it provides various information, depending on its' purpose. As the main focus of this research, Halal portal is created in order to provide information related to Halal, from Halal issues to Halal products and its' manufacturers. The lack of research towards trust-inducing interface elements on Halal portal has lead to the cause of this study. This research is seen important, as it identifies user's interface requirement for Halal portal in Malaysia and trust-inducing interface elements for informational sites such as portals. These identification processes has led to the creation of a proposed user's interface design based on trust-inducing elements and user requirement in the Halal portal. This study has specified its' scope to the people in Shah Alam and the related organization, besides focusing on Halal portal from the aspect of trust. The interface design is the main outcome of this research, excluding the content of the rest of the portal. Besides benefiting Muslims in Malaysia, it indirectly benefits the non-Muslims, by exposing them towards the Halal products in Malaysia. Companies could promote their company and product to the public, while related organizations such as Jabatan Kemajuan Islam Malaysia (JAKIM) can expose more of their site to the public by providing a link in the Halal portal to their respected site. In sum, many parties can gain many benefit through the Halal portal. Interface requirements and trust elements were obtained through research questionnaire, while the design of the portal was created by using Dreamweaver 8.0. Modified model from Technology Acceptance Model (TAM) is adapted in this study, including extraction from a trust-inducing feature's framework. The results obtained was analyzed and led to the design of the trust-inducing Halal portal.